Faktor Determinan Ketepatan Waktu Penyampaian Laporan Keuangan Perusahaan Pertambangan di Indonesia - Marfuah Marfuah; Sakilah Sakilah; Priyono Puji Prasetyo (Wahana Riset Akuntansi, 2021)
This study aims to analyze the effect of profitability, firm size, institutional ownership, audit committee, audit opinion, and company age on the timeliness of financial report submission. The sample used in this study consisted of 26 mining companies listed on the Indonesia Stock Exchange for the period 2015-2018. The sampling method in this study was using purposive sampling method, so 104 samples were selected for 4 years. Hypothesis testing is done using logistic regression. The results of this study indicate that profitability has a significant positive effect on the timeliness of submitting financial statements, while company size, institutional ownership, audit committee, audit opinion and company age have no significant effect on the timeliness of submitting financial reports to mining companies in Indonesia. The results of this study contribute to report users that profitability is an important factor in encouraging the timeliness of the submission of corporate financial reports. Keywords: Audit Committee; Audit Opinion; Institutional Ownership; Profitability; Timeliness.